Evaluation and analysis of emotional intelligence, mood and coping strategies in two Spanish dance companies - de las Heras Fernández, Rosa; Espada-Mateos, María; Carrascal Domínguez, Silvia; García Coll, M. Virginia (Research in Dance Education, 2021)
The aim of this study was to differentiate professional dancers from two different Spanish dance companies with regard to the effects of emotional intelligence, mood and coping strategies, by analysing the existing interrelationship between them. The sample was composed of 36 dancers: 16 women and 20 men aged 19 to 40. Twenty of them came from the national company and 16 from a private Spanish dance company. The questionnaires on mood measures Profile Mood State Questionnaire (POMS), Emotional Intelligence Questionnaire in Sport (IED) and coping strategies for stress (ACSI- 28) were applied. The study indicates that some important differences were found between the men and women dancers with regard to goal setting. In the future, analyses will be able to provide a further development in psychological aspects in order to improve training plans and professional strategies in dancing.
Keywords: spanish dance; emotional intelligence; mood; coping strategies; National Ballet; WOS; Scopus